The night house - Nesbø, Jo, 1960- (Alfred A. Knopf, 2023)
"From the internationally best-selling author, a twisted, multi-layered spin on the classic horror novel In the wake of his parents' tragic deaths in a house fire, fourteen-year-old Richard Elauved has been sent to live with his aunt and uncle in the remote, insular town of Ballantyne. Richard quickly earns a reputation as an outcast, and when a classmate named Tom goes missing, everyone suspects the new, angry boy is responsible for his disappearance. No one believes him when he says the telephone booth out by the edge of the woods sucked Tom into the receiver like something out of a horror movie. No one, that is, except Karen, a beguiling fellow outsider who encourages Richard to pursue clues the police refuse to investigate. He traces the number that Tom prank called from the phone booth to an abandoned house in the Black Mirror Wood. There he catches a glimpse of a terrifying face in the window. And then the voices begin to whisper in his ear... You know who I am. She's going to burn. The one you love is going to burn. There's not a thing you can do about it. When another classmate disappears, Richard must find a way to prove his innocence--and preserve his sanity--as he grapples with the dark magic that is possessing Ballantyne and pursuing his destruction. Then again, Richard may not be the most reliable narrator of his own story..."--